1996
DOI: 10.2307/3433158
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Benzene Metabolism

Abstract: Benzene toxicity involves both bone marrow depression and leukemogenesis caused by damage to multiple classes of hematopoietic cells and a variety of hematopoietic cell functions. Study of the relationship between the metabolism and toxicity of benzene indicates that several metabolites of benzene play significant roles in generating benzene toxicity. Benzene is metabolized, primarily in the liver, to a variety of hydroxylated and ring-opened products that are transported to the bone marrow where subsequent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 16 publications
2
131
0
3
Order By: Relevance
“…Just as benzene can show effect of its own directly, it or its metabolites can do so by binding to tissue protein, DNA and RNA. Previous studies showed that the toxic metabolites of benzene formed covalent bonds on the proteins of liver, kidney and stomach organs, as well as binding with DNA and RNA (Lindstrom et al 1997;Snyder and Hedli 1996). In other study, Turhan and Dere (2007) investigated the effects of benzene on activity of adenosine deaminase (ADA), which is an important enzyme of purine metabolism, in serum, liver, and kidney of rats.…”
Section: Discussionmentioning
confidence: 98%
“…Just as benzene can show effect of its own directly, it or its metabolites can do so by binding to tissue protein, DNA and RNA. Previous studies showed that the toxic metabolites of benzene formed covalent bonds on the proteins of liver, kidney and stomach organs, as well as binding with DNA and RNA (Lindstrom et al 1997;Snyder and Hedli 1996). In other study, Turhan and Dere (2007) investigated the effects of benzene on activity of adenosine deaminase (ADA), which is an important enzyme of purine metabolism, in serum, liver, and kidney of rats.…”
Section: Discussionmentioning
confidence: 98%
“…The metabolism of benzene in humans is not fully characterized but several pathways have been proposed (Medinsky et al, 1996;Smith, 1996;Snyder & Hedli, 1996). One metabolic pathway involves the initial metabolism of benzene in zone III of the liver, mainly by CYP2E1, to produce phenol and hydroquinone.…”
mentioning
confidence: 99%
“…One metabolic pathway involves the initial metabolism of benzene in zone III of the liver, mainly by CYP2E1, to produce phenol and hydroquinone. Free hydroquinone may leave the liver and reach the bone marrow, in which it can be further metabolized to the genotoxic 1,4 benzoquinone metabolite by myeloperoxidase (Snyder & Hedli, 1996). Benzoquinones are potent genotoxic and haematotoxic compounds which can be reconverted to less toxic hydroxy metabolites by NAD(P)H:quinone oxidoreductase (Smith et al, 2001).…”
mentioning
confidence: 99%
“…Peroxidases are hemoprotein enzymes occurring in neutrophils and eosinophils, starting at the promyelocyte, and their enzymatic activity increases along with the maturation of cells. There are reports that the peroxidase of macrophages of the marrow stromal may take part in oxidizing quinone metabolites of benzene and, thus, mediate its hematotoxicity [12,34,35]. Liberation of lipoxin A4 by ASA decreases activity of myeloperoxidase and also influences chemotaxis and stimulation of leukocytes [17,36].…”
Section: Discussionmentioning
confidence: 99%
“…Hematotoxic activity of benzene involves both, the solvent and its metabolites. Induction of the cytochrome P-450 system, especially CYP 2E1 and CYP 2B1, which participates in metabolic activation of benzene, may lead to intensification of the observed alterations [11][12][13]. It has been demonstrated that acetylsalicylic acid (ASA), a widely used non-steroid anti-inflammatory drug, induces cytochrome P-450.…”
Section: Introductionmentioning
confidence: 99%